Spectral characteristics of 5-hydroxymethylfurfural as a related substance in medicinal products containing glucose - Nataliia Hudz; Dmytro Leontiev; Piotr P. Wieczorek (Pensoft Publishers, 2019)
Objectives: To study 5-hydroxymethylfurfural (5-HMF) spectral characteristics aiming at their future application in analytical procedures and their validation for the determination of 5-HMF in liquid products containing glucose after sterilization. Method: Direct spectrophotometric method for the determination of 5-HMF using the molar absorption coefficient at the absorption maximum (284 nm). Results and discussion: aqueous 5-HMF solutions have strong absorption in the ultraviolet range below 310 nm and give two absorption maxima at wavelengths of 229-230 nm and 284 nm. An excellent linear relationship between absorbance and 5-HMF concentration was observed in the concentration range of 2.0-10.0 mg/l. The linear dependence passes through the origin. The molar absorption coefficients of 5-HMF were determined and found to be 3007 mol−1•L•cm−1at 229-230 nm and 16070 mol−1•L•cm−1at 284 nm. The use of the molar absorption coefficient of 5-HMF stated in the Pharmacopeia of the United States of America for determining 5-HMF in polydextrose (16830 mol−1·L·cm−1at 283 nm) gives recovery results for model solutions of reference substance of 5-HMF that are acceptable from the point of view of the requirements of the State Pharmacopeia of Ukraine for methods of quantitative determination of impurities. However, other values of the molar absorption coefficient (17000 and 22700 mol−1•L•cm−1) given in the scientific publications are unsuitable for the quantitative determination of 5-HMF as an impurity in medicinal products. Conclusion: The molar absorption coefficient (16830 mol−1•L•cm−1at 284 nm) may be used to quantify 5-HMF as an impurity in medicinal products containing glucose. For a specific medicinal product, a full validation of the analytical procedure of the 5-HMF determination is required taking into account the composition of this product.